Employee ownership and performance of state-owned entities of Pakistan: a moderated mediation analysis of psychology ownership, loyalty, motivation and satisfaction. - Javed, Tariq (Tanjong Malim, 2021)
Employee ownership and performance of state-owned entities of Pakistan: a moderated mediation analysis of psychology ownership, loyalty, motivation and satisfaction. by Javed, Tariq